2009
DOI: 10.1590/s1516-14392009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Changes on transmittance mode of different composite resins

Abstract: The purpose of this study was to evaluate the transmittance of seven different composite resins. Ten specimens were prepared (10 mm diameter, 2 mm thickness) for each experimental group, as follows: G1- Charisma® A2 (Heraeus-Kulzer); G2- FiltekTM Supreme A2E (3M/ESPE); G3- FiltekTM Supreme A2B (3M/ESPE); G4-FiltekTM Supreme YT (3M/ESPE); G5- Esthet-X® A2 (Dentsply); G6- Esthet-X® YE (Dentsply); G7- Durafill® A2 (Heraeus-Kulzer) and G8- FiltekTM Z-100 A2 (3M/ESPE). The transmittance mode was measured using a UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Carefully modulated optical properties, such as color, translucency, fluorescence, and opalescence, are needed to offer a natural appearance to the tooth (Arimoto et al, ; Queiroz et al, ; Yu, Lim, & Lee, ); such properties are controlled by the depth and kinetics of polymerization (Howard, Wilson, Newman, Pfeifer, & Stansbury, ; Kawaguchi, Fukushima, & Miyazaki, ). Differences in the composition of composite resins, in particular with respect to their organic matrix, dispersed filler particles, pigments, and modifiers, are also responsible for the variation of such properties (Song, Yu, Ahn, & Lee, ; Woo, Yu, Ahn, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…Carefully modulated optical properties, such as color, translucency, fluorescence, and opalescence, are needed to offer a natural appearance to the tooth (Arimoto et al, ; Queiroz et al, ; Yu, Lim, & Lee, ); such properties are controlled by the depth and kinetics of polymerization (Howard, Wilson, Newman, Pfeifer, & Stansbury, ; Kawaguchi, Fukushima, & Miyazaki, ). Differences in the composition of composite resins, in particular with respect to their organic matrix, dispersed filler particles, pigments, and modifiers, are also responsible for the variation of such properties (Song, Yu, Ahn, & Lee, ; Woo, Yu, Ahn, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the transmission of light energy into the composites may be diminished by the increase in darkness of the composite shade [35] (Figure 7). Furthermore, dark pigments of a color modifier may block the light penetration or increase the light scattering due to the increase in refractive index mismatch in the composites [9,36,37]. It was reported that the color pigments may act as the light-scattering centers, which could reduce light penetration into the composites in a dose-dependent manner [38].…”
Section: Discussionmentioning
confidence: 99%
“…The specimens were prepared using a polished Teflon™ matrix of 4.0 mm depth and 10.0 mm internal diameter 15,[19][20][21][22] in which the composite resin was added. Thus, 20 specimens were prepared using Filtek™ Bulk-Fill composite resin (3M ESPE), and the other 20 specimens used Filtek™ Z350 XT composite resin (3M ESPE).…”
Section: Methodsmentioning
confidence: 99%